CHILDREN’S GAMES IN EDUCATION: KI HADJAR DEWANTARA’S PERSPECTIVE AND ITS RELEVANCE IN LEARNING - Chasanah, Iflahathul (Institut Agama Islam Riyadlatul Mujahidin Ngabar (IAIRM) Ponorogo, 2021)
Abstract Education for children must be formed following the characteristics of students. One of the characteristics of children is to play games. Games for children are an educational process. Along with the development of the times, education no longer accommodates the characteristics of students, it has a tendency to develop one of the three potentials. The impact is the dehumanization process. One alternative to bridge this gap is to re-introduce and re-implement traditional games that have been formalized by Ki Hadjar Dewantara through the Taman Siswa's curriculum. Ki Hadjar Dewantara argued that the game is an education for children. The game can be done through Panca Indera exercises, children can develop their natural potential in a balanced manner. These potentials include the potential of cognitive (cipta), affective (rasa), psychomotor (karsa) so that it accommodates all the potential of his soul. Various studies have proven the fact that traditional games have many benefits for students' personal development and the development of learning's curriculum. Therefore, traditional games can be used in the learning process at this time.